2004
DOI: 10.1210/me.2003-0178
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Progression and Activation of Akt Kinase Are Required for Insulin-Like Growth Factor I-Mediated Suppression of Apoptosis in Granulosa Cells

Abstract: Ovarian follicle development is dependent on growth factors that stimulate cell proliferation and act as survival factors to prevent apoptosis of follicle cells. We examined the mechanism of the protective effect of IGF-I against Fas ligand-induced apoptosis of granulosa cells and its relationship to cell proliferation. IGF-I activated both the phosphoinositide 3'-OH kinase (PI3K) and the MAPK pathways. Experiments using specific inhibitors of these pathways showed that protection by IGF-I was mediated by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
89
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 51 publications
5
89
0
Order By: Relevance
“…Whereas Akt overexpression is mainly associated with an oncogenic phenotype, this pathological context is usually associated with mutation or modification of the expression of other components of the Akt pathway, such as PI3K and/or phosphatase and tensin homologue deleted on chromosome 10 (Luo et al, 2003). Besides, the dual involvement of Akt in mediating proliferative and/or antiapoptotic responses has to be considered inasmuch as both responses are intricate (Hu et al, 2004). Zhu et al (2004) reported that Gab2 overexpression, which enhanced the phosphorylation of Akt but not of ERK1/2, reduced cell proliferation induced by granulocyte colony-stimulated factor (Zhu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas Akt overexpression is mainly associated with an oncogenic phenotype, this pathological context is usually associated with mutation or modification of the expression of other components of the Akt pathway, such as PI3K and/or phosphatase and tensin homologue deleted on chromosome 10 (Luo et al, 2003). Besides, the dual involvement of Akt in mediating proliferative and/or antiapoptotic responses has to be considered inasmuch as both responses are intricate (Hu et al, 2004). Zhu et al (2004) reported that Gab2 overexpression, which enhanced the phosphorylation of Akt but not of ERK1/2, reduced cell proliferation induced by granulocyte colony-stimulated factor (Zhu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…During the first gap phase or G1, cells are quiescent but potentially receptive to mitogenic stimuli, which stimulate cells to embark into the proliferative phases of the cell cycle consisting of the DNA synthesis phase (S), the second gap phase (G2), and the mitotic phase (M). In granulosa cells of the developing follicle, the G1/S transition phase is a critical checkpoint, as progression from the quiescent stage (G0/G1) to the S phase requires the action of cell proliferation and survival factors such as insulin-like growth factor-1 (IGF1) and estradiol (E 2 ; Hu et al 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Such activation is correlated with cell survival in a wide variety of cells, including those of epithelial, mesenchymal and neuronal origin [9,10], as well as cancer cells [11]. In bovine granulosa cells, Akt, a downstream substrate of PI3K, was necessary for the protective effect of IGF-1 against FasL-induced apoptosis [12]. Akt has been also demonstrated to be involved in granulosa cell survival in hens [6] and pigs [13].…”
Section: Introductionmentioning
confidence: 99%